Analisis Keabsahan Smart Contract dalam Perjanjian Bisnis di Indonesia - Dethan, Jecelyn Amanda; Irianto, Yerica Evadne Giraldani (Universitas Ekasakti, 2024)
This study aims to examine the validity of smart contracts in business agreements in Indonesia as seen from the provisions of the agreement in the Civil Code and the provisions of contracts in other regulations applicable in Indonesia. The method used in this study is the normative method, which focuses on examining the rules in positive law. Based on this study, it is concluded that the use of smart contracts in Indonesia has been implemented properly and when viewed from the perspective of Civil Law in Indonesia, the use of smart contracts has fulfilled the elements of an agreement in Article 1320 of the Civil Code in general, although there are still shortcomings such as automatic execution as if made by only one party. In addition, in reality it is difficult to fulfill some of its elements, such as smart contracts creating special challenges because the transactions carried out in them are not bound by national borders, given the differences in legal systems between Indonesia and other countries. In all its limitations, smart contracts can still be carried out in Indonesia because of the principle of freedom of contract which has been regulated in Article 1338 of the Civil Code. In practice, the principle of freedom of contract must take into account Article 18 paragraph (1) and paragraph (2) of Law Number 8 of 1999 concerning Consumer Protection.